VARIATION IN THE SIZE OF THE CORKSCREW-SHAPED OR SPIRAL GLANS PENIS IN LANDRACE AND DUROC BOARS - I Nyoman Wiku Wedatama; I Nengah Wandia; I Wayan Bebas (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Pigs are an important commodity in Bali, where the reproductive performance of boars plays a key role in productivity. The boar glans penis has a corkscrew-shaped structure that is essential for copulation; however, information regarding size variation among strains remains limited. This study aimed to identify and compare variations in spiral length, diameter, and number of turns of the glans penis in Landrace and Duroc boars. Present study employed an analytical observational design using a convenience sampling method with 12 adult boars (seven Landrace and five Duroc). Samples were collected post-mortem from a pig slaughterhouse in Bali. Morphometric measurements were performed using a digital caliper, and data were analyzed using an independent t-test (α = 0.05). The results showed that the mean spiral length of the glans penis in Landrace boars was 39.511 ± 1.184 mm, while in Duroc boars it was 38.090 ± 0.849 mm (p > 0.05). The mean spiral diameter was 15.935 ± 0.948 mm in Landrace boars and 15.856 ± 1.138 mm in Duroc boars (p > 0.05). The number of spiral turns was identical in both strains, with a mean value of one turn. In conclusion, there were no statistically significant differences in spiral length, diameter, or the number of turns of the glans penis between Landrace and Duroc boars.